CXCR7 Antagonism Reduces Acute Lung Injury Pathogenesis - Pouzol, Laetitia; Sassi, Anna; Baumlin, Nadège; Tunis, Mélanie; Strasser, Daniel S.; Lehembre, François; Martinic, Marianne M. (Frontiers in Pharmacology, 2021)
Loss of control in the trafficking of immune cells to the inflamed lung tissue contributes to the pathogenesis of life-threatening acute lung injury (ALI) and its more severe form, acute respiratory distress syndrome (ARDS). Targeting CXCR7 has been proposed as a potential therapeutic approach to reduce pulmonary inflammation, however its role and its crosstalk with the two chemokine receptors CXCR3 and CXCR4 via their shared ligands CXCL11 and CXCL12 is not yet completely understood. The present paper aimed to characterize the pathological role of the CXCR3/CXCR4/CXCR7 axis in a murine model of ALI. Lipopolysaccharide (LPS) inhalation in mice resulted in the development of key pathologic features of ALI/ARDS, including breathing dysfunctions, alteration of the alveolar capillary barrier and lung inflammation. LPS inhalation induced immune cell infiltration into the bronchoalveolar space, including CXCR3+ and CXCR4+ cells, and enhanced the expression of the ligands of these two chemokine receptors. The first-in-class CXCR7 antagonist, ACT-1004-1239, increased levels of CXCL11 and CXCL12 in the plasma without affecting their levels in inflamed lung tissue, and consequently reduced CXCR3+ and CXCR4+ immune cell infiltrates into the bronchoalveolar space. In the early phase of lung inflammation, characterized by a massive influx of neutrophils, treatment with ACT-1004-1239 significantly reduced the LPS-induced breathing pattern alteration. Both preventive and therapeutic treatment with ACT-1004-1239 reduced lung vascular permeability and decreased inflammatory cell infiltrates. In conclusion, these results demonstrate a key pathological role of CXCR7 in ALI/ARDS and highlight the clinical potential of CXCR7 antagonism in ALI/ARDS pathogenesis.